Serum free light chain measurements to reduce 24‐h urine monitoring in patients with multiple myeloma with measurable urine monoclonal protein. Issue 10 (15th August 2018) - Tschautscher, Marcella; Rajkumar, Vincent; Dispenzieri, Angela; Lacy, Martha; Gertz, Morie; Buadi, Francis; Dingli, David; Hwa, Lisa; Fonder, Amie; Hobbs, Miriam; Hayman, Suzanne; Zeldenrust, Stephen; et al.
Abstract: Detection of myeloma progression (PD) relies on serial 24‐h urinary M protein measurements in patients without measurable serum M spike. We examined whether serial difference free light chain (dFLC) levels could be used as a surrogate for serial 24‐h urine M protein measurements in monitoring for PD in patients with baseline measurable urine M protein. We studied 122 patients who had serial measurement of urine M protein and serum FLC and had demonstrated PD. The median increase in dFLC with progression as defined by urine M spike was 110% (IQR: 55‐312) and median absolute increase was 74 mg/dL; while 89% of patients had dFLC increase ≥ 25%, 94% had absolute increase in dFLC > 10 mg/dL, and 98% met at least 1 of these 2 criteria at PD. In patients with baseline measurable serum FLC ( n = 118), 89% had increase in dFLC ≥ 25%, 97% had dFLC increase of > 10 mg/dL, and 98% had 1 of the 2. We conclude that serial dFLC assessments can be used in place of serial 24‐h urine protein assessments during myeloma surveillance to monitor for PD. Once patients have an absolute increase in dFLC of >10 mg/dL from the nadir, a 24‐h urine collection can then be assessed to document PD as per the International Myeloma Working Group criteria.